Polish Space Agency – an outline of the legal and financial issues - Jacek Wantoch-Rekowski; Robert Kwaśniewski; Martyna Wilmanowicz (Prawo Budżetowe Państwa i Samorządu, 2018)
The article examines the legal and financial issues of the Polish Space Agency. It indicates the aim of establishing the Agency and its tasks. It analyses the Agency in terms of regulations concerning executive agencies (included in the Act on Public Finances). In addition, the article examines the financial management of the Agency – on the level of both the Act on the Polish Space Agency and the Agency’s financial plans published annually in Annex 11 to the Budget Act, and on the basis of the results of the Supreme Audit Office inspection carried out in this entity.